2009
DOI: 10.1523/jneurosci.1286-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Spectrotemporal Interactions Underlying Selectivity for Complex Sounds in Auditory Cortex

Abstract: In the auditory cortex of awake animals, a substantial number of neurons do not respond to pure tones. These neurons have historically been classified as "unresponsive" and even been speculated as being nonauditory. We discovered, however, that many of these neurons in the primary auditory cortex (A1) of awake marmoset monkeys were in fact highly selective for complex sound features. We then investigated how such selectivity might arise from the tone-tuned inputs that these neurons likely receive. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
141
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(165 citation statements)
references
References 46 publications
15
141
9
Order By: Relevance
“…The majority of neurons in our study were recorded at superficial cortical depths, most likely in layers II/III (median relative depth: 0.2 mm for HTNs and 0.3 mm for non-HTNs). A previous study in awake marmosets found a high proportion of combination-selective, nontoneresponsive, and low spontaneous-firing neurons at superficial cortical depths in A1 (49). A two-photon imaging study showed that A1 neurons in layer IV respond more strongly to pure tones than neurons in upper layers (56).…”
Section: Discussionmentioning
confidence: 86%
“…The majority of neurons in our study were recorded at superficial cortical depths, most likely in layers II/III (median relative depth: 0.2 mm for HTNs and 0.3 mm for non-HTNs). A previous study in awake marmosets found a high proportion of combination-selective, nontoneresponsive, and low spontaneous-firing neurons at superficial cortical depths in A1 (49). A two-photon imaging study showed that A1 neurons in layer IV respond more strongly to pure tones than neurons in upper layers (56).…”
Section: Discussionmentioning
confidence: 86%
“…In 2 animals (M57U and M77W), the CI electrode was inserted into an otherwise intact cochlea. In the other 2 animals (M5X and M3Y), the cochlea was deafened just before electrode insertion with multiple intrascalar injections of neomycin sulfate (10% solution), which is toxic to hair cells (Nuttall et al, 1977). Perilymph was gently removed by suction at the cochleostomy margin, and the cochlea was filled with neomycin solution using a flexible syringe inserted through the cochleostomy.…”
Section: Methodsmentioning
confidence: 99%
“…Although the mechanism by which combination sensitivity (CS) is directionally selective in the temporal domain is not fully understood, some propositions exist (22)(23)(24)(25)(26). As an empirical matter, direction selectivity is clearly present early in auditory cortex (19,27). It is also observed to operate at time scales (50-250 ms) sufficient for phoneme concatenation, as long as 250 ms in the zebra finch (15) and 100 to 150 ms in macaque lateral belt (18).…”
mentioning
confidence: 99%
“…Primate electrophysiology identifies CS as occurring as early as core's supragranular layers and in lateral belt (16,17,19,37). In the macaque, selectivity for communication calls-similar in spectrotemporal structure to phonemes or consonant-vowel (CV) syllables-is observed in belt area AL (54) and, to an even greater degree, in a more anterior field, RTp (55).…”
mentioning
confidence: 99%